Exploring the companion of Ostrowskis inequalities via local fractional integrals - Saleh, Wedad; Meftah, Badreddine; Lakhdari, Abdelghani; Kiliçman, Adem (New York Business Global LLC, 2023)
This paper investigates the companion of Ostrowski's inequality in the framework of fractal sets. First, a new identity related to local fractional integrals is introduced, serving as the foundation for establishing a set of inequalities applicable to functions with generalized $s$-convex and $s$-concave derivatives. An illustrative example is presented to validate the obtained results, demonstrating their accuracy. Additionally, the paper discusses several practical applications, highlighting the significance of the established inequalities. The research presented in this paper contributes to the growing field of studying functions on fractal sets, which has attracted considerable interest from scientists and engineers.